REORIENTASI PROFIL LULUSAN DAN REFORMASI KURIKULUM SOLUSI LULUSAN TERSERAP LAPANGAN KERJA - Barnad Barnad; Edith Primadiana Tedjokusumo (Politeknik Ubaya, 2023)
Education as a means to increase knowledge and skills and can improve welfare. The higher the level of education, the more experience one gets and the more complex the problems that can be solved, and this has an impact on increasing income. Advances in information and communication technology have changed human civilization. The development of science and technology has made how many jobs done by humans have been taken over by machines so that the remaining work is very little and more specific for humans to do. The curriculum given to the students aims to provide a variety of knowledge and skills so that they can complete various assignments and be placed in various positions. This condition does not meet the needs of the world of work today, because workers only do specific jobs. Another challenge is that several large companies no longer require a diploma for their prospective workers; instead, it is based on the skills certification mastered by future workers. This phenomenon is a challenge for education providers to reorient the profile of graduates who have been determined. One way is to reform the curriculum to improve the student's skills and mastery of digital information literacy, data processing, visualization, and modern office technology so that graduates can work in the modern office era. The narrative above is the premise of the descriptive research that the writer conducted based on various sources of documentation, literature, and questionnaire results from alumni.